Florida’s Marine Sponges - John Stevely; Don Sweat (EDIS, 2009)
SGEF-169, a 4-page fact sheet by John Stevely and Don Sweat, describes why study and management of sponge populations remains essential to the health of Florida’s coastal waters and discusses their potential pharmaceutical value, harvesting practices, their history, biology, and other interesting facts. Published by the Florida Sea Grant Program, December 2008.